Ponticola hircaniaensis sp. nov., a new and critically endangered gobiid species (Teleostei: Gobiidae) from the southern Caspian Sea basin - Zarei, Fatah; Esmaeili, Hamid Reza; Kovačić, Marcelo; Schliewen, Ulrich K.; Abbasi, Keyvan (Zootaxa, 2022)
Ponticola hircaniaensis sp. nov. is described as a new gobiid species from the Kaboudval Stream, southern Caspian Sea basin. The new species is diagnosed among Caspian Sea basin Ponticola species by the following combination of characters: second dorsal-fin branched rays 14–16, anal-fin branched rays 10–12, scales in lateral series 52–59; lower jaw slightly, if at all, prognathous; head and body yellowish brown showing a reticulate brown pattern on a yellow background, first dorsal fin with a marginal bright orangish-yellow band and a dark anterior spot, upper part of pectoral-fin base with a distinct dark brown stripe; length of third spine in first dorsal fin 13.4–18.3 % of standard length (SL), second dorsal-fin spine length 11.1–13.8 % SL, caudal peduncle length and depth 16.4–20.1 % and 11.1–12.8 % SL, respectively, head depth at nape 70.9–81.0 % of head length (HL), and at eye 52.5–66.0 % HL; sagittal otolith dorsal rim with a broad concavity in the middle, dorsal depression absent or indistinct, sulcus length/sulcus height and sulcus height/otolith height ratios 1.47–1.82 and 0.34–0.40, respectively. It is also characterised by a K2P nearest neighbour distance of 5% to P. kessleri in the mtDNA COI barcode region. Mitochondrial and nuclear DNA analyses suggested extensive hybridization between P. hircaniaensis sp. nov. and P. gorlap at Kaboudval, providing evidence for the first record of hybridization in the Ponto-Caspian gobiids. Based on narrow geographic range isolated above the Zarrin Gol Dam (< 2 km2), extensive hybridization with P. gorlap, and other threats, the new species should be considered Critically Endangered.